Born into prostitution the Badis of Nepal. - Films for the Humanities & Sciences (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 2007)
"A daughter of a Badi prostitute is required to be registered under the surname Nepali. So marked from birth, she is born into prostitution and is expected to follow her mother into that trade-unless the family, the Dalit community, or charitable NGOs are moved to help them make a change. This program profiles two Badi families and the positive efforts of one former prostitute and Suklal Nepali, director of SAFE (Social Awareness for Education), to assist them. Ironically, it is a sex customer, through his blunt appraisal of Badi prostitutes, who inadvertently speaks the most eloquently of these women's plight. "
Title from the container.
Electronic reproduction
Keywords: Caste -- India; Dalit -- India; India -- Scheduled tribes